The task and solution of normalization of appeals in the management system - Akhmedova, Iroda (MMIT Proceedings, 2024)
In this thesis, the author expresses his opinion on the tasks and possibilities of the electronic government system in the management of the issues set for the development of the electronic government system in the "Digital Uzbekistan - 2030" Strategy. It describes the indicators of the e-government development index.